The saving cross of the suffering Christ : the death of Jesus in Lukan soteriology - Wilson, Benjamin R., 1983- (Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche ;, 2016)
"Through an exegetical analysis of the passion references in Luke and Acts, this book shows how Luke presents the death of Jesus both as a mechanism of atonement within God's plan of salvation and as a marker of Jesus' identity as the messiah. In the process, the book also helps to locate Luke's thought within the broader landscape of first century Jewish and Christian practice and belief"--Back cover.